2016
DOI: 10.1111/cas.12969
|View full text |Cite
|
Sign up to set email alerts
|

World Health Organization grade IIIII astrocytomas consist of genetically distinct tumor lineages

Abstract: Recent investigations revealed genetic analysis provides important information in management of gliomas, and we previously reported grade II–III gliomas could be classified into clinically relevant subgroups based on the DNA copy number aberrations (CNAs). To develop more precise genetic subgrouping, we investigated the correlation between CNAs and mutational status of the gene encoding isocitrate dehydrogenase (IDH) of those tumors. We analyzed the IDH status and CNAs of 174 adult supratentorial gliomas of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The proportion of the TP53 germline variant reads was increased in the mother's tumor sample ( Fig. 2 A; Supplemental Table 1 ), suggesting copy-neutral loss of the wild-type variant, which is commonly observed in Grade II–III diffuse gliomas ( Hattori et al 2016 ). This was indeed the case according to the copy-number analysis that utilized both sequence coverage and heterozygous allele frequencies in the germline ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The proportion of the TP53 germline variant reads was increased in the mother's tumor sample ( Fig. 2 A; Supplemental Table 1 ), suggesting copy-neutral loss of the wild-type variant, which is commonly observed in Grade II–III diffuse gliomas ( Hattori et al 2016 ). This was indeed the case according to the copy-number analysis that utilized both sequence coverage and heterozygous allele frequencies in the germline ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Histological grade, although suffering from inter-and intraobserver variability as well as tissues sampling error, especially in grade II and III tumors [6][7][8][9] is still recognized as an important characteristic for classification of CNS tumors. According to the new 2016 WHO classification, diffuse astrocytoma (WHO grade II) and anaplastic astrocytoma (WHO grade III) are now divided in two sub-categories depending on the mutation of the IDH family of genes (IDH1, IDH2): IDH-mutant and IDH-wildtype.…”
Section: Introductionmentioning
confidence: 99%
“…The patient improved with regard to sensory aphasia following surgery. Postoperative pathological analysis revealed that the tumor was an astrocytoma (using World Health Organisation grade II) (12).…”
Section: Resultsmentioning
confidence: 99%